2016
DOI: 10.1016/j.bbamcr.2016.05.012
|View full text |Cite
|
Sign up to set email alerts
|

A novel regulatory role for tissue transglutaminase in epithelial-mesenchymal transition in cystic fibrosis

Abstract: Cystic fibrosis (CF) is a genetic disorder caused by mutation of the cystic fibrosis transmembrane conductance regulator (CFTR) for which there is no overall effective treatment. Recent work indicates Tissue Transglutaminase (TG2) plays a pivotal intracellular role in proteostasis in CF epithelia and that the pan TG inhibitor cysteamine improves CFTR stability. Here we show TG2 has another role in CF pathology linked with TGFβ1 activation and signalling, induction of Epithelial-Mesenchymal Transition (EMT), CF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…It is also well reported that TGFβ1 can specifically induce TG2 expression [26], which we have confirmed in RKO and SW480 cells. Importantly, the specific effects of TGFβ1 on TG2 induction could be blocked by a TGFβ neutralizing antibody in these two cell lines.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…It is also well reported that TGFβ1 can specifically induce TG2 expression [26], which we have confirmed in RKO and SW480 cells. Importantly, the specific effects of TGFβ1 on TG2 induction could be blocked by a TGFβ neutralizing antibody in these two cell lines.…”
Section: Discussionsupporting
confidence: 88%
“…Treatment of SW620 and SW480 (Figure 2B and 2C) with the TG2 selective inhibitor 1-155 [2426] also reduced the expression of TG2 and EMT markers— vimentin and FN in SW480 and SW620 cells, and the expression of transcription factors Slug and Twist 1 in SW620 cells. 1-155 treatment also enhanced expression of the epithelial marker ZO-1 in both cell lines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…CF affects not only the physiological function of lungs, but also the pancreas, liver and intestines (22,28). In our study, CFTR was the hub protein in the PPI network, had the highest connectivity with 182 genes (Figure 2).…”
Section: Discussionmentioning
confidence: 59%